The Plain Language of Love and Loss : A Quaker Memoir - Taylor, Beth, 1953- (Book collections on Project MUSE., 2009)
"A memoir of the author's Pennsylvania Quaker family and the shadow cast on it by her brother's suicide at age fourteen during the tumultuous Vietnam War era. Taylor grapples with understanding the complexities of religious heritage, pacifism, and patriotism as she places her family's story within the context of recent American history"--Provided by publisher.